Curcumin supplementation accelerates high-altitude acclimatization, prevents polycythemia and modulates gut microbiota in male Han population: a randomized controlled trial - Hu, Jilei; Lang, Hongmei; Fan, Die; Wen, Ting; Shi, Jiaojiao; Xiao, Chunxiu; Li, Yunming; Kang, Chao; Shi, Peijie; Shen, Lirong; Lin, Ning (Frontiers in Nutrition, 2025)
BackgroundPrevious evidence showed that curcumin enhanced the oxygen supply efficiency of hemoglobin and alleviated acute plateau hypoxia injury in animal models. However, its efficacy on human beings is not yet verified. This study aimed to assess the effects of curcumin supplementation on hypoxia injury and gut microbiota in the male Han population.MethodsIn this 7-week single-blinded randomized trial, 102 male Han population urgently entered the 3,000 meters altitude from the plain and received 812 mg curcumin or placebo per day for 1 week on the plain and 6 weeks on the plateau. Biochemical parameters were assessed and physical examination was carried out at the baseline (T0), and the end of the 1st (T1) and 7th week (T3) of intervention. The score of acute mountain sickness (AMS) was evaluated in the 2nd week after entering the plateau (T2) and T3. Intestine microbial composition was analyzed by metagenomic sequencing.ResultsAfter a 1-week intervention on the plain, curcumin significantly increased red blood cells (RBC), hematocrit (HCT), and hemoglobin in treatment group as compared to placebo group (p < 0.05). However, curcumin significantly reduced the levels of HCT and hemoglobin compared to that in the placebo group after the 6-week intervention on the plateau (p < 0.05). Furthermore, the score of AMS in the curcumin group were lower than those in the placebo group at T3, although with no significant difference. Gut microbiota analysis indicated that curcumin significantly increased the abundance of butyrate-producing bacteria Roseburia, Lachnospira, and Sellimonas while decreasing the abundance of Alistipes and Escherichia at high-altitude environments. In addition, a higher relative abundance of Bifidobacterium was observed in the curcumin group on the plateau.ConclusionCurcumin exhibited different regulation of hemoglobin in low- and high-altitude environments. On the plain, curcumin supplementation elevated the RBC and hemoglobin, which is favorable for reducing the incidence of AMS at the early stage of entering the plateau. On the plateau, curcumin suppressed excessive increase of HCT and hemoglobin by modulating the abundance of butyrate-producing bacteria to avoid the occurrence of high-altitude polycythemia.Clinical trial registrationhttps://www.chictr.org.cn/, identifier: ChiCTR220005965.